The effect of extraction of impacted third molars with temporomandibular joint disorders: Pengaruh ekstraksi gigi molar ketiga impaksi dengan gangguan sendi temporomandibula - Azkia Ulil Azmy; Rasmi Rikmasari; Setyawan Bonifacius (Makassar Dental Journal PDGI Makassar, 2023)
The extraction of impacted third molars is one of the most common treatments performed in oral and maxillofacial surgery. Most third-molar surgeries are performed without complications, although still can cause serious complications in patients, one of are temporomandibular joint disorders (TMD). This study aims to determine the effect of third molar extraction on TMD that con-ducted using preferred reporting items for systematic reviews and meta-analyses (PRISMA) protocol through the databases PubMed, Ebsco, Sage, Scopus, and Springer with relevant keywords and published 2012-2022. The articles were then selected and evaluated eligibility. Detailed data extracted by google spreadsheet. Six articles were included in this rapid review, consisted of retrospective study (n=1), prospective cohort study (n=1) retrospective cohort study (n=1), review (n=2), and syste-matic review (n=1). It is concluded that there was an effect but not significant between extraction of impacted third molars and TMD related to various influencing factors. These factors include the complexity of the procedure, age, and gender. There is no definitive relationship due to the variation in the sample and research methods, and no quality assessment was conducted.